Parkinson's Disease Is Associated with Impaired Gut–Blood Barrier for Short‐Chain Fatty Acids - Yang, Xiaodong; Ai, Penghui; He, Xiaoqin; Mo, Chengjun; Zhang, Yi; Xu, Shaoqing; Lai, Yiqiu; Qian, Yiwei; Xiao, Qin (Movement disorders, 2022)
ABSTRACT Background Short‐chain fatty acids (SCFAs) produced by gut microbiota are reduced in feces but paradoxically increased in plasma of patients with Parkinson's disease (PD), which may stem from intestinal wall leakage. Gut function should be taken into consideration when conducting microbial‐metabolite research. Objective The objective was to investigate synchronous changes of SCFAs in feces and plasma of patients with PD, taking constipation as a confounder to better disentangle the SCFA metabolism exclusively associated with PD. Methods The concentrations of fecal and plasma SCFAs in 33 healthy control subjects and 95 patients with PD were measured using liquid and gas chromatography mass spectrometry, respectively. Patients with PD were divided into patients with PD without constipation (n = 35) and patients with PD with constipation (n = 60). Gut–blood barrier (GBB) permeability was assessed by plasma/fecal ratio of SCFA concentrations and fecal α1‐antitrypsin concentration. Results Patients with PD displayed decreased concentrations of fecal acetic, propionic, and butyric acid and increased concentrations of plasma acetic and propionic acid. Fecal acetic, isobutyric, and isovaleric acid were lower and plasma acetic and propionic acid were higher in patients with PD with constipation than in patients with PD without constipation. Constipation aggravated GBB permeability in patients with PD. Combined fecal and plasma SCFAs could discriminate patients with PD from healthy control subjects. Fecal SCFAs, except propionic acid, were negatively correlated with disease severity, while plasma acetic, propionic, and valeric acid showed a positive correlation. Conclusions Our study showed alterations of fecal and plasma SCFAs in patients with PD that were associated with an impaired GBB and might be aggravated by constipation. © 2022 International Parkinson and Movement Disorder Society.